Pengaruh Pernikahan Dini Terhadap Laju Ekonomi Masyarakat Di Kelurahan Bendung - Risma Yanti; Desty Endrawati Subroto; Nasywa Roudhotul; Siti Ika Mudrika; Aris Widodo; Ziaul Fatwa Andini Yusuf (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of early marriage is still common in various regions in Indonesia, including Bendung Village, Kasemen District, Serang City. This practice is not influenced by a single factor but rather the result of a combination of interrelated elements. Low levels of education mean that many adolescents, especially girls, lack the knowledge and skills to delay marriage and pursue career opportunities. Economic pressure within the family is also often cited as a reason, with parents believing that marrying off their children at a young age can reduce financial burdens. Furthermore, strong cultural norms and values, including the belief that early marriage can maintain family dignity, further reinforce this practice. This study aims to assess the impact of early marriage on the economic development of the local community. The method used in this study is a quantitative approach using simple linear regression analysis. A total of 60 respondents who married before the age of 19 served as the research sample. Normality tests showed that the collected data were normally distributed, making them suitable for further analysis. The results of the regression analysis indicate that early marriage has a significant impact on the community's economic condition, with a significance value of 0.018. These findings indicate a clear relationship between the high rate of early marriage and the decline in the economic conditions of families in the area.